Correction: Bucki et al. Bactericidal Properties of Rod-, Peanut-, and Star-Shaped Gold Nanoparticles Coated with Ceragenin CSA-131 against Multidrug-Resistant Bacterial Strains. Pharmaceutics 2021, 13, 425 - Sylwia Joanna Chmielewska; Karol Skłodowski; Joanna Depciuch; Piotr Deptuła; Ewelina Piktel; Krzysztof Fiedoruk; Patrycja Kot; Paulina Paprocka; Kamila Fortunka; Tomasz Wollny; Przemysław Wolak; Magdalena Parlinska-Wojtan; et al. (MDPI AG, 2024)
In the original publication [...]